(untitled) (Bangladesh Medical Journal Khulna, 2012)
Cervical pregnancy is a rare variety of Ectopic pregnancy. It is a life threatening form of ectopic pregnancy. The diagnosis of cervical pregnancy can be missed by an unsuspecting mind inspite of the routine use of first trimester Ultrasonography. Careful evaluation is necessary for immediate proper management of such case. DOI: http://dx.doi.org/10.3329/bmjk.v44i1-2.10474 Bang Med J (Khulna) 2011: 44(1&2) 28-30